Effects of nine weeks isokinetic training on power, golf kinematics, and driver performance in pre-elite golfers - James Parker; Charlie Lagerhem; John Hellström; M. Charlotte Olsson (BMC, 2017)
Abstract Background It has previously been shown that isotonic strength training can improve driver performance among golfers, though few studies have investigated effects of strength training on swing kinematics together with driver performance. In this study we investigated whether isokinetic rotational training could improve driver performance and swing kinematic variables amongst elite golfers. Methods Twenty competitive pre-elite golfers (handicap better than −3.0), 13 men and 7 women, were split into two groups, one group received the isokinetic power training (IK) alongside their normal isotonic pre-season strength-training and the other group continued with their normal isotonic pre-season strength-training regime (IT). The IK group completed 12 sessions of isokinetic power training on a standing rotation exercise (10% body weight at 1 m/s) and barbell squat (25 kg plus 10% body weight at 0.5 m/s). The IT group continued with their normal isotonic pre-season strength-training regime. Participants were tested for rotational power, lower body power, golf swing kinematics, and driver performance before and after a nine-week training period. Results After the nine-week training period both the IK and the IT groups increased their dominant side rotational force and power (effect sizes between 0.50-0.96) and magnitude based inference indicated that IK had a likely (> 80%) more beneficial increase in dominant side rotational force and power. For swing kinematics, IK had a likely (> 80%) more beneficial improvement in lead arm speed and acceleration compared to the IT group. For driver performance, IK had a possible (65%) beneficial effect on ball speed and likely (78%) beneficial effect on carry distance when compared to IT, whereas neither of the groups improved club head speed. Conclusion In the present study on pre-elite golfers we found that 9 weeks of isokinetic training increased seated rotational force and power, peak arm speed and arm acceleration, ball speed, and carry distance more compared to isotonic training. Even though isokinetic training did not increase CHS, it did result in greater carry distance.